Therapeutic effect of cataract surgery with simultaneous intravitreal injection of aflibercept on diabetic macular edema: An observational study. Issue 33 (19th August 2022) - Yen, Chu-Yu; Yen, Ju-Chuan; Chen, Chun-Chen; Hu, Hsiao-Yun; Cheng, Feng-Shiang; Tseng, Po-Chen
Abstract : This study aimed to investigate the therapeutic effect of cataract surgery along with simultaneous intravitreal injection (IVI) of aflibercept on diabetic macular edema (DME). This cohort study enrolled 106 patients aged >40 years with type 2 diabetes mellitus and DME who received cataract surgery from January 1, 2016, to October 31, 2020. The baseline and mean data of the following parameters were collected: age, sex, glycated hemoglobin level, diabetic retinopathy (DR) grading, previous DR treatments including IVI of anti–vascular endothelial growth factor and pan-retinal photocoagulation, intraocular pressure, use of intraocular pressure-lowering medication, central subfield thickness (CST), and log MAR visual acuity (VA). Patients were categorized into 2 groups based on whether they received aflibercept IVI or not during cataract surgery and were compared using the t test and Fisher exact test for continuous and discrete variables, respectively. Beta coefficient and standard error were calculated using multiple linear regression analysis to identify the explanatory variables predictive of the net change of CST and log MAR VA. There was no difference in the net change in CST (15.24 ± 45.07 μm vs 18.62 ± 33.84 μm, P = .772) and log MAR VA (−0.27 ± 0.29 vs −0.37 ± 0.31, P = .215). Gender, glycated hemoglobin level, aflibercept IVI during cataract surgery, and baseline CST did not interfere with the morphological and functional outcomes of DME in cataract surgery. Older age was significantly and independently associated with a greater net change in log MAR VA. Proliferative DR was significantly and independently associated with a greater net change in CST and log MAR VA. A greater baseline log MAR VA was significantly and independently associated with lower net change in log MAR VA. Simultaneous aflibercept IVI for treating DME may not interfere with the functional and tomographic parameters of cataract surgery relative to cataract surgery alone. Factors influencing the outcomes of patients with DME undergoing cataract surgery are as follows: age, baseline DR staging, and baseline VA. Identifying these factors of DME preoperatively may be an important consideration in preventing it from progressing and for improving the overall visual prognosis.